Effects of chemical and mechanical stimulation on laryngeal motion during anaesthetic induction with alfaxalone, thiopentone or propofol in healthy dogs - Dzikiti, Tarisai Brighton (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2018.